New challenges for head teachers in Hungarian schools - Szabó, Mária (Vodenje v vzgoji in izobraževanju, 2014)
After a period of twenty years, when shared responsibility and local autonomy characterized Hungarian educational administration, the government decided to improve the quality of education by strengthening the role of the state. Since the end of 2011 several actions have been taken to attain this purpose. This article draws a parallel between the role of head teachers in the decentralized and that of the centralized system of educational administration, and it gives an overview of the activities of the present government of education. It sums up the main elements of the triangle of support, assessment and qualification, focusing on the possible new roles of head teachers in it.
Keywords: assessment; Hungary; Madžarska; principals; profesionalni razvoj; qualification; ravnatelji; role; strokovna usposobljenost; support; vodenje